2009
DOI: 10.1007/s10562-008-9801-1
|View full text |Cite
|
Sign up to set email alerts
|

How Gold Deposition Affects Anatase Performance in the Photo-catalytic Oxidation of Cyclohexane

Abstract: Gold deposition on Hombikat UV100 was found to negatively affect the activity of this Anatase catalyst in selective photo-oxidation of cyclohexane. By ammonia TPD and DRIFT spectroscopy it was determined that the Au deposition procedure leads to a significant decrease in OH-group density (mol m -2 BET ) on Hombikat, suggesting that the amount of surface OH-groups, rather than the presence or absence of Au, is determining the catalytic performance. The importance of surface OH-groups was demonstrated by compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 34 publications
(49 reference statements)
2
72
0
Order By: Relevance
“…The catalytic data indicate that the introduction of gold nanoparticles on the TiO2 surface seems to increase the hydrophilicity of the photocatalyst and, as a consequence, the capability of Au-TiO2 to adsorb CO2 was diminished. Carneiro et al reported that gold nanoparticles are able to modify hydroxyl group's population on titania [88]. Hence, it can be proposed that the different surface properties of CuO-TiO2 and Au-TiO2 play a key role in the reaction, as revealed by the different photocatalytic behaviour displayed by the two photocatalysts.…”
Section: Effect Of the Promoters On The Properties And Activity Of Thmentioning
confidence: 99%
“…The catalytic data indicate that the introduction of gold nanoparticles on the TiO2 surface seems to increase the hydrophilicity of the photocatalyst and, as a consequence, the capability of Au-TiO2 to adsorb CO2 was diminished. Carneiro et al reported that gold nanoparticles are able to modify hydroxyl group's population on titania [88]. Hence, it can be proposed that the different surface properties of CuO-TiO2 and Au-TiO2 play a key role in the reaction, as revealed by the different photocatalytic behaviour displayed by the two photocatalysts.…”
Section: Effect Of the Promoters On The Properties And Activity Of Thmentioning
confidence: 99%
“…On the other hand, Au/TiO 2 shows higher UV light‐induced activity than that of pristine TiO 2 , primarily because of the increase in the charge separation efficiency by the interfacial electron transfer from TiO 2 to Au 22. 23 However, there are recent reports describing that Au nanoparticle loading can decrease the photocatalytic activity of TiO 2 under visible24 and UV light irradiation 25. 26 Moreover, the UV light‐induced photocatalytic activity of Au nanoparticles due to the interband transition has also been reported 19.…”
Section: Introductionmentioning
confidence: 99%
“…One is to prepare small TiO 2 particles with a very large surface area, which can exhibit superior performance over bulk materials [16]. The other is to modify the band gap of TiO 2 by doping other elements [17][18][19], sensitizing with dyes [20][21][22], and grafting heteronanostructure [23,24]. Especially, metal-semiconductor heteronanostructure as an effective photocatalysis has attracted great attention for air and water purification due to the strong oxidizing properties and stability under UV irradiation [24][25][26].…”
Section: Introductionmentioning
confidence: 99%